PERBEDAAN HASIL BELAJAR KOGNITIF MATEMATIKA MENGGUNAKAN DISCOVERY LEARNING DAN PROBLEM BASED LEARNING SISWA KELAS V SEKOLAH DASAR - Rini Budiwati; Sutama Sutama; Markhamah Markhamah (Autentik : Jurnal Pengembangan Pendidikan Dasar, 2022)
The purpose of this research is to see how Discovery Learning and Problem Based Learning affect students' grades or the end of learning aspects of knowledge in fifth grade elementary school students. Quantitative research methods with an experimental approach. The grouping of data used is descriptive statistics. The research tools used are tests and documentation. The participants in this research were students of fifth grade elementary school. Samples or research subjects were taken randomly. From the research results, both Problem Based Learning and Discovery Learning products in studying have increased. However, the Problem Based Learning (PBL) strategy is superior in strengthening students' cognitive learning products in Mathematics compared to Discovery Learning. (DL). This is evidenced by the fact that the experimental population research subjects using Problem-Based Learning outperformed the population sample using Discovery Learning Keywords: problem based learning, discovery learning, cognitive learning outcomes